Transition from conventional to modern water management in Pakistan - Khan A.H.; Munir S.; Mahmood S.; Turral H. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
The continuous supply-based irrigation system of Upper Swat Canal in Pakistan with a water allowance of 0.28 litres per second per ha and about 80 to 100 percent cropped area during a year has been remodelled and modernized for carrying increased water allowance of 0.70 litres per second per ha. The new management intensive crop-based operations of the system have not been fully ensured due to lack of understanding of the new concept, lack of commitment and political interference. Results from field data revealed that a slow departure has been made from conventional to more advanced strategies, where the average delivery performance ratio at selected offtake heads before and after introducing the new operations was 0.67 and 0.84, respectively. Farmers refused water with return flow to drains as high as 62 percent of net deliveries during summer 2003 which dropped to about 21 percent in summer 2004 due to improved operations.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)